Associations between a patient-reported outcome (PRO) measure of sarcopenia and falls, functional status, and physical performance in older patients with cancer. Issue 6 (November 2015) - Gewandter, Jennifer S.; Dale, William; Magnuson, Allison; Pandya, Chintan; Heckler, Charles E.; Lemelman, Tatyana; Roussel, Breton; Ifthikhar, Rafa; Dolan, James; Noyes, Katia; Mohile, Supriya G.
Abstract: Objective : In older patients with cancer, we aimed to investigate associations between a patient-reported outcome measure for sarcopenia (SarcoPRO) and the Short Physical Performance Battery (SPPB), self-reported falls, and limitations in instrumental activities of daily living (IADLs). Materials and Methods : Assessments were conducted as part of the initial evaluation of older, often frail, patients with cancer seen in the Specialized Oncology Care and Research in the Elderly (SOCARE) clinic. Univariate associations were evaluated using Spearman's correlation and Wilcoxon sign ranked tests. Logistic regressions were used to identify associations of clinical factors and SarcoPRO scores or SPPB scores with falls and IADL limitations. Results : In total, 174 older patients with cancer were evaluated. A moderate correlation was found between the SarcoPRO and the SPPB (ρ = 0.62). After adjusting for multiple clinical factors, neither the SarcoPRO nor the SPPB were associated with falls. In contrast, both higher SarcoPRO (i.e., worse) and lower SPPB (i.e., worse) scores were associated with limitations in IADLs (odds ratio for one unit change in predictor: SarcoPRO: 1.06, p < 0.0001; SPPB: 0.71, p = 0.003, respectively). Models using the SarcoPRO and SPPB explained similar amounts of variability in association with IADL limitations (AUC: 0.88 vs. 0.87, respectively). Conclusions : The SarcoPRO was moderately associated with the SPPB, an objective measure of physical performance, and was associated with limitations in IADLs. Thus, older patients with cancer who present with IADL limitations should be screened for sarcopenia. The SarcoPRO shows promise as a measure for screening as well as outcome assessment for research on sarcopenia.